A DESCRIPTIVE CATALOGUE OF PICTURES, POETICAL AND HISTORICAL INVENTIONS - Blake, William (Fragmentum, 2014)
Painted by William Blake, in Water Colours, Being the Ancient Method of Fresco Painting Restored: and Drawings, For Public Inspection, and for Sale by Private Contract, At N 28 Corner of Broad Street-Golden Square London; Printed by D. N. Shury, 7, Berwick-Street, Soho, for J. Blake, 28, Broad-Street, Golden-Square. 1809.